The Effects of Global Climate Warming on the Developmental Parameters of Helicoverpa armigera (Hübner, 1808) (Lepidoptera: Noctuidae) - Zhiqian Liu; Biyu Liu; Huan Yu; Honghua Zhang; Zhipeng He; Zhihang Zhuo (Insects)
Helicoverpa armigera (Hübner, 1808) is a significant global agricultural pest, particularly posing a major threat during the boll-forming stage of cotton. In recent years, the severity of its damage has increased markedly, and its population dynamics and biological characteristics may be profoundly affected by global climate change. This study conducted a systematic meta-analysis to evaluate the life history traits of H. armigera under conditions of rising global temperatures, different photoperiods, and humidity levels. A comprehensive analysis of 26 related studies revealed that different developmental stages of H. armigera have distinct temperature requirements. When the temperature is within an optimal range (32 °C to 35 °C), the development rate of H. armigera accelerates, the life cycle shortens, and the reproductive capacity of female moths increases. However, when the temperature exceeds 35 °C, development slows, mortality rates increase, and the oviposition of female moths decreases significantly, indicating a negative impact of high temperatures on growth and reproduction. Overall, as the temperature rises above 20 °C, various physiological indicators of H. armigera significantly improve, and at 32 °C, the larval development period and overall life cycle reach their shortest duration. This meta-analysis provides new insights into the biological responses of H. armigera in the context of climate change and offers a scientific basis for future control strategies.